Exploring rural secondary school students' attitude toward the Malayan tapir through salient beliefs - Lim, Evelyn Ai Lin; Mariapan, Manohar; Ang, Yvonne Su Ming; Abi, Jane; Aziz, Azlizam; Hussin, Mohamed Zakaria (Forestry Department Peninsular Malaysia, 2013)
Environmental education programmes in Malaysia have been successful in increasing students' knowledge but not so in changing attitudes. To design educational programmes that changes attitudes, we need to understand the underlying determinant of attitude. The purpose of the study was to explore and elicit rural secondary school students' attitudes towards the Malayan tapir through their salient beliefs. Focusing on the cognitive and affective components of the attitude model, eighty-one secondary school students were asked to elucidate what they knew about the Malayan tapir through pictorial stimulation in focus group discussion. Students were observed to be intrigued by the physical characteristics of the Malayan tapir but knew little about its ecological function, natural habitat and threats while displaying positive and negative emotions in reaction to the pictures. Future research implications include the designing of an environmental education programme based on the observations of this study and measuring the effectiveness of the programme in influencing behaviour.